2015
DOI: 10.1002/anie.201410967
|View full text |Cite
|
Sign up to set email alerts
|

Electron Tunneling Rates in Respiratory Complex I Are Tuned for Efficient Energy Conversion

Abstract: Respiratory complex I converts the free energy of ubiquinone reduction by NADH into a proton motive force, a redox reaction catalyzed by flavin mononucleotide(FMN) and a chain of seven iron–sulfur centers. Electron transfer rates between the centers were determined by ultrafast freeze-quenching and analysis by EPR and UV/Vis spectroscopy. The complex rapidly oxidizes three NADH molecules. The electron-tunneling rate between the most distant centers in the middle of the chain depends on the redox state of cente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 42 publications
3
65
0
Order By: Relevance
“…Today long-range electron tunnelling is thought to occur in many proteins, and seems to be enhanced by particular molecules, such as the aromatics–which occur more frequently in oxidoreductases, which are key components of respiratory chains [47]. Crucially, it is now thought that electron tunnelling plays an important role in how mitochondria produce energy [48,49] and ensures a tight coupling between electron flow and protonation via a process known as ‘redox tuning’ [50]. In effect, electron tunnelling appears to be a pivotal component of mitochondrial function.…”
Section: The Quantum Anglementioning
confidence: 99%
“…Today long-range electron tunnelling is thought to occur in many proteins, and seems to be enhanced by particular molecules, such as the aromatics–which occur more frequently in oxidoreductases, which are key components of respiratory chains [47]. Crucially, it is now thought that electron tunnelling plays an important role in how mitochondria produce energy [48,49] and ensures a tight coupling between electron flow and protonation via a process known as ‘redox tuning’ [50]. In effect, electron tunnelling appears to be a pivotal component of mitochondrial function.…”
Section: The Quantum Anglementioning
confidence: 99%
“…In the hydrophilic domain, a chain of 8-9 iron-sulfur (FeS) centers connects the NADH/flavin mononucleotide (FMN) site with the Q site (11,25,26), which locates approximately 30 Å above the membrane surface (14). The FeS centers form an electron conduction wire, in which the eT takes place on a microsecond-millisecond timescale between the two ends of the hydrophilic domain (27,28).…”
mentioning
confidence: 99%
“…It therefore seems that long-range electron tunnelling may occur in many proteins, in particular in oxidoreductases and key components of respiratory chains [46] and thus may be important in how mitochondria produce energy [46,47], ensuring a tight coupling between electron flow and protonation via redox tuning [48]. It is now also thought that photosynthesis utilises fundamental quantum principles, involving coherence and excitons to transfer energy efficiently [38,39,41] This is especially interesting as lysozyme appears to demonstrate a Fröhlich condensate; Fröhlich suggested that terahertz radiation could be absorbed by proteins leading to them behaving as a series of coupled oscillators generating a macroscopic quantum effect [49].…”
Section: The Emergence Of Quantum Biologymentioning
confidence: 99%